Effects of hole arrangement and trenched hole on multirow film cooling - Wen Wang; Jiahuan Cui; Shaoxing Qu (AIP Advances, 2022)
Multirow film cooling is an advanced cooling method to provide effective surface cooling for gas turbine components exposed to high temperature. In this paper, the performance of multirow film cooling under different configurations is investigated numerically. The geometrical parameters, including the hole arrangement, hole orientation, and trenched hole, are considered. The numerical setup is validated before the performances of different cooling configurations are compared. The flow and heat transfer characteristics of the various cooling configurations are analyzed, and the different row-to-row interactions are revealed. For the configurations with standard holes, the staggered arrangement of simple angle holes achieves better cooling efficiency than the counterpart with inline configuration, while the inline arrangement with opposite compound angle holes provides the best cooling efficiency. For the configurations with trenched holes, the trench promotes the coolant uniform mixing, and the coolant stays more close to the effusion plate. Thus, the multirow cooling efficiency with trenched holes is better than the cooling configurations with standard holes.